CHARACTERISATION OF MICROBIAL LIPASES FROM VEGETABLE OIL POLLUTED SOIL (2014)
Vegetable oil spills are becoming frequent and are potentially more challenging than petroleum hydrocarbon spills. Microbial lipases occupy a place of prominence among biocatalysts and are often used for remediation of vegetable oil spills. There is a need for extensive characterisation of lipase for the treatment of vegetable oil-polluted sites. This work was carried out to characterise lipases from lipolytic isolates and as well monitor the degradation pattern of vegetable oil. Microorganisms were isolated from eight experimental soil samples contaminated with different types of vegetable oil, soil from an oil mill in Ibadan, and normal uncontaminated soil as a control. The isolates were characterised, identified, and screened for lipase production using standard methods. Temperature, pH and ion concentration (NaNO3 and MgSO4) were optimised for the lipase activity. A bacterium and a yeast with highest lipase activity, determined using a titrator were selected for further work. These enzymes were partially purified by dialysis, column and ion-exchange chromatography. Their purity and molecular weight were determined by Sodium dodecyl sulfate polyacrylamide gel electrophoresis, and their kinetics were studied. The ability of the isolates to degrade olive oil in the laboratory was monitored at five-day intervals for 25 days using two mineral salt media. Concentration of the olive oil and microbial load were monitored in the media. The fatty acid profiles were determined using gas chromatography. Data obtained were analysed using ANOVA. Seventy-three microorganisms were isolated from the contaminated soils and identified as species of Bacillus (16), Pseudomonas (12), Flavobacterium (6), Alcaligenes (2), Proteus (3), Micrococcus (1), Aspergillus (9), Penicillium (6), Mucor (4), Rhizopus (2) Streptomyces (2), Candida (4), Saccharomyces (4), Geotrichum (1), Kluveromyces (1). Crude enzymes of Pseudomonas fluorescens and Candida parapsilosis had the highest lipase activity of 0.8 U/mL and 0.4 U/mL respectively. Temperature, pH, and ion concentration (NaNO3 and MgSO4) which had optimum enzyme activities for partially purified Pseudomonas fluorescens (0.85 U/mL), were 27 oC, 7.5 and 0.05 mM, and Candida parapsilosis (0.35 U/mL), were 35 oC, 6.5 ± 7.5, and 0.05 mM respectively. The molecular mass of the purified P. fluorescens and C. parapsilosis lipases were 45 and 38 KDa respectively. The purified P. fluorescens and C. parapsilosis lipases had Km values of 0.8 and 1.4 mg/mL, and Vmax of 0.7 and 1.1 g/sec respectively. There was a (P < 0.05) significant reduction in the concentration of the residual oil by P. fluorescens on day 15 (0.0031 mol/L) compared to day 0 (0.0064 mol/L). The plate counts, 8.8 ± 0.03 and 10.3 ± 0.03, were (P < 0.05) significantly low on day 5 for both organisms compared to day 25. The percentage reduction of fatty acid by P. fluorescens and C. parapsilosis after 20 days was 8.2 % and 6.7 % respectively in the media used. Lipases from Pseudomonas fluoresecens and Candida parapsilosis had potential for the degradation of fatty waste. They could therefore be employed in environmental clean up of vegetable oil spill site.